PRAGMATISME DAN KONSEP SEKOLAH ISLAM TERPADU - Dwi Septiawati; Agus Suradika (Perspektif, 2022)
Abstrak Sekolah Islam Terpadu hadir sebagai respons keprihatinan atas sistem pendidikan di Indonesia yang belum berhasil mencapai hakikat tujuan pendidikan. Sekolah Islam Terpadu memadukan secara integratif nilai dan ajaran Islam dalam bangunan kurikulum dengan pendekatan pembelajaran yang efektif dan pelibatan yang optimal dan kooperatif antara guru dan orang tua, serta masyarakat untuk membina karakter dan kompetensi peserta didik. Sekolah Islam Terpadu dianggap mengembangkan konsep pendidikan pragmatis yang menjadikannya sekolah eksklusif dan mahal. Tulisan ini menjelaskan: pertama, konsep pragmatisme dalam perspektif pemikir Barat dan perspektif pemikir Islam yang diwakili oleh Ibnu Khaldun; kedua, bagaimana konsep pragmatisme memberi kerangka dasar dalam konsep Sekolah Islam Terpadu, baik dalam tujuan mau pun proses pendidikan. Abstract Integrated Islamic Schools exist as a response to concerns over the education system in Indonesia which has not succeeded in achieving the nature of educational goals. The Integrated Islamic School integrates Islamic values and teachings in an integrated manner in curriculum building with an effective learning approach and optimal and cooperative involvement between teachers and parents, as well as the community to foster the character and competence of students. Integrated Islamic Schools are considered to develop the concept of pragmatic education which makes them exclusive and expensive schools. This paper explains: first, the concept of pragmatism in the perspective of Western thinkers and the perspective of Islamic thinkers represented by Ibn Khaldun; second, how the concept of pragmatism provides the basic framework for the concept of an Integrated Islamic School, both in terms of goals and in the educational process.